2019
DOI: 10.1007/jhep05(2019)066
|View full text |Cite
|
Sign up to set email alerts
|

Two-loop doubly massive four-point amplitude involving a half-BPS and Konishi operator

Abstract: The two-loop four-point amplitude of two massless SU(N) colored scalars and two color singlet massive particles with different virtuality described by a half-BPS and Konishi operators is calculated analytically in maximally supersymmetric Yang-Mills theory. We verify the ultraviolet behaviour of the unprotected composite operator and exponentiation of the infrared divergences with correct universal values of the anomalous dimensions in modified dimensional reduction scheme. The amplitude is found to contain lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

6
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 88 publications
(143 reference statements)
0
12
0
Order By: Relevance
“…Since form factors involve both local operators and asymptotic on-shell states, they contain important information of both on-shell amplitudes and anomalous dimension of local operators. This has inspired many studies that generalize amplitudes techniques to form factors and also use form factors to study the spectrum problem of generic operators [34][35][36][37][38][39][40][41][42][43][44]. A state-of-the-art pedagogical review for form factors in N = 4 SYM can be found in [45].…”
Section: Introductionmentioning
confidence: 99%
“…Since form factors involve both local operators and asymptotic on-shell states, they contain important information of both on-shell amplitudes and anomalous dimension of local operators. This has inspired many studies that generalize amplitudes techniques to form factors and also use form factors to study the spectrum problem of generic operators [34][35][36][37][38][39][40][41][42][43][44]. A state-of-the-art pedagogical review for form factors in N = 4 SYM can be found in [45].…”
Section: Introductionmentioning
confidence: 99%
“…In refs. [118,119], it has been shown that the conjecture also fails to hold true for two-point FF with two operators insertion. In view of this, we investigate whether there is any similarity between the HT weight terms of the scalar and pseudo-scalar FF as computed in this article and that of mSYM theory.…”
Section: Behaviour Of Leading Transcendentality Weight Termsmentioning
confidence: 99%
“…The technicalities of the computation of bare amplitudes closely follow the steps used in the recent calculation of two-point form factors with two-operator insertion with different virtualities in maximally supersymmetric Yang-Mills theory [21]. Feynman diagrams are generated symbolically using QGRAF [22].…”
Section: Computation Of the Amplitudesmentioning
confidence: 99%